Design of PI and PID Control System for Induction Motor Control on Gamma Irradiator Characterization Prototype Using a Modified Ziegler-Nichols Method - Rissa Damayanti; Beny Syawaludin; Hyundianto Arif Gunawan (Journal of Electrical Technology UMY, 2022)
The irradiator simulator's induction motor drive control system is carried out to maintain safety and accuracy in the loading/unloading process and product transportation system. Control is done by maintaining the speed of the induction motor at a certain speed so that the travel time for the loading/unloading process is predetermined. This study aims to answer the existing problems using the PI and PID control systems and prove that using the control system will give better results than the current system applications. In this study, the gain configuration for the PI controller that best fits the design requirements is obtained at a Kp value of 0.038, a Ki of 2.18, and a Phase Margin ( ) of 70°, resulting in a motor rotational speed that can achieve stability at the set point determined by the setting time is 0.90 seconds. The maximum overshoot is 0% and has a steady state error value of 0.00013. Then the gain configuration for the PID controller that best fits the design requirements is obtained at a value of Kp of 0.0066, Ki of 10.85, Kd of 9.9x10-7 and with a Phase Margin ( )  of 50°, resulting in a motor rotational speed that is high. Able to achieve stability at the specified set point with a setting time of 0.63 seconds and a maximum overshoot of 0%, the steady state error value of 0.00013. From the results obtained, it can be seen that this PI and PID control method can be used as an alternative control system on the induction motor drive system on the irradiator simulator. The controller can control the system according to the specified conditions so that the irradiation process time accuracy improves or increases.